Implementasi Metode Rabbani dalam Pembelajaran Tahfidz Al-Qur'an Santriwati Kelas XII - Siti Ratna Maria; Lalu Supriadi Bin Mujib; Abdul Azis (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The aims of this research was to know the implementation of the Rabbani method in learning of the tahfidz Al-Qur'an at the Al-Ikhlas Taliwang Modern Islamic Boarding School and Nurul Haramain NW Narmada Modern Islamic Boarding School, the obstacles and solutions. This research was qualitative research with multi-site study design. Data collection was carried out through observation, in-depth interviews, and documentation. Determination of informants used purposive sampling technique. Data analysis used interactive analysis techniques by Miles Hubermen and Saldana. The results of the research showed that: 1) Implementation of the Rabbani method in learning of tahfidz Al-Qur'an at Al-Ikhlas Taliwang Modern Islamic Boarding School and Nurul Haramain NW Narmada Modern Islamic Boarding School for females agreed with steps and stages contained in the instructions of use of the Rabbbani method, 2) Internal obstacles: the students did not master makharijul huruf and tajwid, forgot, and did not focus. External obstacles: the difficulty in distinguishing the similar verses, the difficulty in dividing the time and the limited number of teachers who master the Rabbani method. 3) Solutions: providing of motivation, internal approach, reading improvement (tahsin) of Al-Qur'an, tahfidz contact book, delivering the memorization (tasmi'), memorization repetition (muraja'ah), training of the Rabbani method, study visits, and taking notes on similar verses.